Dynamics of Audiens Interpretation and Reception of Korean Drama Queen of Tears - Tabitha Hemastuti; Roro Retno Wulan (Lingkar Studi Komunikasi (LISKI), 2025)
The popularity of Korean dramas as part of the Hallyu Wave has grown significantly in Indonesia, creating a cultural phenomenon where audiences do not only consume content but also actively interpret and engage with it. One of the recent dramas, Queen of Tears, sparked intense fan reactions, particularly on social media, due to its emotionally rich narrative and depiction of modern marital struggles. This phenomenon raises a central research problem: how do audiences from different social backgrounds decode and interpret the messages presented in the drama? Using Stuart Hall’s encoding/decoding theory and a qualitative descriptive method with a phenomenological approach, this study investigates the audience reception of Queen of Tears by conducting in-depth interviews with eight informants who are active fans of the drama. The findings show varied interpretations across three decoding positions: dominant, negotiated, and oppositional, based on the drama’s three main themes: romance and sacrifice, family and social pressure, and throne and power. The majority of informants were in dominant and negotiated positions, indicating general acceptance with contextual adjustments. This study highlights that audience reception is not linear, but shaped by individual experiences, values, and socio-cultural context. It contributes to understanding how media texts like Queen of Tears act as spaces for meaning negotiation and emotional reflection among Indonesian viewers.